Algal Stem Blotch in Southern Highbush Blueberry in Florida - Douglas Phillips; Norma Flor; Philip Harmon (EDIS)
Algal stem blotch has become a significant disease on southern highbush blueberries (SHB) in Florida. It can cause stunted growth and leaf yellowing, as well as increased susceptibility to Botryosphaeria, in some cases leading to plant death. Information contained in this publication is intended for Florida blueberry growers to use as a guide in the identification and management of algal stem blotch on SHB.